IDENTITY AND DIALOGUE. A CATHOLIC PERSPECTIVE ON MISSIONS AND PARISHES IN THE DIASPORA - KAPTIJN, Astrid (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2018)
When focusing on the Catholic view regarding mission and parishes in the diaspora, the author of this paper emphasizes some aspects of the historical development concerning this vision. The paper starts with a short overview of some historical tendencies and highlights the latest events and document of the Catholic Church regarding this issue. A first characteristic of the Catholic view on migration concerns the terminology. When speaking about missions and parishes, the author uses these notions in the sense of Church structures. The Catholic Church designates the local structures that are not yet parishes with the word missions. In the Catholic view, it has a specific significance, but the author underlines that the missionary perspective is not entirely absent from this Catholic point of view.